Biodiversity of ecotypes and aggressivenss ranges of Moniliophthora perniciosa, in Theobroma cacao L. national of the Ecuadorian Coast - Auhing Arcos, Javier Andrés (2021)
The objective of the work was focused on studying the biodiversity of ecotypes and aggressiveness ranges of Moniliophthora perniciosa, in Theobroma cacao. Plant material with the presence of the pathogen from 12 plantations of T. cacao L Nacional was sampled, analyzing its morphological characteristics, identification by PCR and the aggressiveness of the disease in national cacao EET-19. The basidiocarps differ in size and basidiospore production considering the strain MpLRBF-105 with the largest diameter of basidiocarp and basidiospore discharge. The basidiocarps differ in size and basidiospore production considering the strain MpLRBF-105 with the largest diameter of basidiocarp and basidiospore discharge. The content of lamelulas would be adding the increase of basidiospores in the strains (MpLRBF105 and MpBOLN107), with the largest dimensions between lengths of (11.58 to 12.01 µm) and width (6.23 and 5.95 µm) in the strains (MpLRBA-101, MpLRVE-102, MpLRMO-103, MpGUBA-104, MpLRBF-105 and MpBOLN-107). The genetic characterization of the ITS region of M. perniciosa showed genetic variability with the formation of three Sub-groups, this corresponds to their different agroecological zones of the Ecuadorian Coast. The highest degree of aggressiveness due to M. perniciosa infection gave rise to cotyledonal brooms with (4 to 11 axillary brooms) for the MpLRBF-105, MpGUBA-104, MpLRMO-103, and MpLRVE-102 strains. With 68% inhibition in fresh root weight, strain MpGUBA-104 (Balao). Consequently, the climatic conditions and the pressure to increase commercial plantations of T. cacao CCN-51, are generating changes in the ecology of M. pernciosa.